Transverse susceptibility study of the effect of varying dipolar interactions on anisotropy peaks in a three-dimensional assembly of soft ferrite nanoparticles - Poddar, Pankaj; Morales, Marienette B.; Frey, Natalie A.; Morrison, Shannon A.; Carpenter, Everett E.; Srikanth, Hariharan (Journal of Applied Physics, 2008)
Collective magnetization dynamics in nanoparticle assemblies is of current interest as it forms the basis of high density storage media. It is important to understand how interparticle interactions in a three-dimensional (3D) arrangement of superparamagnetic nanoparticles would affect the overall effective magnetic anisotropy of the system. We have studied the influence of varying strengths of dipolar interaction on the static and dynamic magnetic properties of surfactant-coated monodispersed manganese zinc ferrite nanoparticles using reversible transverse susceptibility. We track the evolution of the anisotropy peaks with varying magnetic field, temperature, and interaction strength. The blocking temperature shows an increase from 28 to 32 K and the coercive field (at 10 K) shows an increase from 144 to 192 Oe as the system changes from the case of weakly interacting to strongly interacting 3D assembly of the particles. (C) 2008 American Institute of Physics. [DOI: 10.1063/1.2977592]

Large magnetocaloric effect, moment, and coercivity enhancement after coating Ni nanoparticles with Ag - Srinath, Sanyadanam; Poddar, Pankaj; Das, Raja; Sidhaye, Deepti; Bhagavatula L. V. Prasad; Gass, James; Srikanth, Hariharan (ChemPhysChem, 2014)
We observe a large magnetocaloric effect in monodisperse Ni and NicoreAgshell nanoparticles in the superparamagnetic region. The organically passivated Ni nanospheres show a large magnetic entropy change of 0.9 J kg(-1)K for a 3 T magnetic field change. In comparison to the surfactant-coated Ni nanoparticles, the NicoreAgshell nanoparticles show an enhanced coercivity, magnetization, and magnetocaloric effect (1.3 kgK for a 3 T magnetic field change). The coercivity at 10 K increases from 360 Oe for Ni nanoparticles to nearly 610 Oe for NicoreAgshell particles. This large enhancement is attributed to the enhanced inter-particle interaction, which is mediated by the metallic shell, over the relatively weaker dipolar interaction in the surfactant-coated Ni nanoparticles, and to modification of the surface spin structure.
Keywords: anisotropy; core-shell; magnetic properties; Nanoparticles; superparamagnetic